As dimensões subjetivas da persuasão no jornalismo: da retórica ao infotenimento no site Catraca Livre - Shinnishi, Eduarda Fernanda Lopes (2019)
The internet and technological innovations have led to changes in the relationship between viewers and media, especially regarding the migration of readers to the digital market. Consequently, these transformations provided new formats for the production and distribution of information and news. In this sense, the communication companies realized that it is essential to adapt to these new demands. Through this, the media companies began to venture on the web, and within this new format is the free Turnstile Portal, a site totally focused on the digital universe. Thus, this study investigates the rhetoric of the Free Turnstile Portal, based on the mapping and analysis of the rhetoric strategies employed by this portal. For this, a bibliographical research was initially carried out, seeking to deepen in the main theories about the approached subject. Then the corpus analysis was performed regarding rhetorical arguments and infotainment journalism. Finally, a portal content analysis was made, object of this work. Based on the results obtained, it can be said that Ratchet Free has strong presence of infotainment on its homepage, with news that can entertain and surprise its reader. It was also observed that the rhetoric and its processes are inculcated in the journalistic practice of this portal, either to persuade the reader with the arguments presented, or by constructing his discourse.